2020
DOI: 10.1111/jonm.13215
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perception regarding patient safety climate and quality of health care in general hospitals in Japan

Abstract: Aim To clarify perceptions of nurses towards patient safety climate and quality of health care in Japan. Background Nurses' perceptions of patient safety climate and quality of health care services are not well‐known. Method The survey was conducted at general hospitals with 200 beds or more using the Patient Safety Climate Scale and the Modified multiple‐item scale for consumer perceptions of health care service quality. Results Significant positive correlations were found among nurses’ perception towards pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
13
1
2
Order By: Relevance
“…However, they reported providing a good quality of care and have no intention of leaving their jobs in the coming year. These results differed from studies that identified the relationship between a negative perception of the patient safety climate and intention to leave one's nursing job 18 and positive perception of the patient safety climate and quality of care, 19 and from the other study that assessed the perception of patient safety at the end of the third wave of the COVID-19 pandemic, resulting in a more positive perception of the patient safety climate. 10 High PPR for most dimensions indicates the need to improve the patient safety culture in the institution.…”
Section: Discussioncontrasting
confidence: 97%
“…However, they reported providing a good quality of care and have no intention of leaving their jobs in the coming year. These results differed from studies that identified the relationship between a negative perception of the patient safety climate and intention to leave one's nursing job 18 and positive perception of the patient safety climate and quality of care, 19 and from the other study that assessed the perception of patient safety at the end of the third wave of the COVID-19 pandemic, resulting in a more positive perception of the patient safety climate. 10 High PPR for most dimensions indicates the need to improve the patient safety culture in the institution.…”
Section: Discussioncontrasting
confidence: 97%
“…Quando as ações envolvem a punição e responsabilização individual há uma deterioração na segurança do paciente e na qualidade dos cuidados, pois reduz a prontidão dos profissionais para relatar incidentes. (27) Nesse aspecto, vale destacar um estudo no qual identificou-se que o reconhecimento de uma cultura justa influencia o empoderamento psicológico de enfermeiros, que, por sua vez, afeta o desenvolvimento de atividades voltadas para a segurança do paciente. (28) Dentre as limitações, destaca-se o recrutamento de instituições para constituírem os cenários de estudo, diante dos cadastros com endereços eletrônicos desatualizados, dificultando a apresentação dos propósitos e do projeto da investigação, assim como o receio demonstrado pelos serviços de diálise em permitir a avaliação de aspectos sensíveis às práticas gerenciais.…”
Section: Discussionunclassified
“…Patient safety and safety climate in healthcare commonly describe safety culture (Olds et al., 2017). This distinctive culture is demonstrated in how the organization and involved individuals conduct and manage risks and safety behaviors (Nakano et al., 2021; Reis et al., 2018). Safety culture is usually evaluated by a valid and reliable safety climate assessment tool (Gehring et al., 2015; Glarcher et al., 2022; Sexton et al., 2006).…”
Section: Introductionmentioning
confidence: 99%